Deen and Dunya: Islam, street spirituality, crime and redemption in English road culture - Reid, Ebony (Theoretical criminology, 2024)
This article presents ethnographic and media analysis that explores how Islam has come to shape conceptions of the material, sacred, crime and redemption in contemporary English street culture. Islam’s clear dichotomy between the mundane ‘Dunya’ and sacred ‘Deen’ shape how socio-economically marginalised, ethnic minority men make sense of the world around them. Stark inequalities have tainted the material world for the UK’s most disadvantaged, prompting them to seek redemption entirely outside it – in the world of the sacred where they can experience warmth. In analysing their experiences we highlight how paths to desistance have arguably been overlooked where analyses of Islam in street culture have focused on questions of radicalisation.